Modeling thermal environment of sunlight-greenhouse with pond for Scylla serrata - SHAO Yu-fang; ZHEN Jin-tu (浙江大学学报. 农业与生命科学版)
Increasing the technical content of seashore aquaculture is an important subject in sea exploitment. Sunlight-greenhouse, which is referred to as a “Chinese-featured horticultural facility”, is very effective on heat preservation and energy saving. Thus it is widely used in planting vegetables and flowers in North China. And its optical and thermal environment and architectural structure have been studied and optimized by several researchers. Raising Scylla serrata in Sunlight-greenhouse with pond (SGP) is a grand new area of the application of sunlight-greenhouse. The thermal environment of SGP is affected by four primary parameters: solar radiation, wind speed, air temperature and relative humidity. It is different from that of the plant greenhouse because of the preservation of heat by the pond. And the pond in SGP is different from the natural pond because of the covering of the greenhouse. A static model of the thermal environment in SGP was established based on the experimental data and the former results of the plant greenhouse and natural pond. Simulation results show good agreement with the experimental values. This research has some sense on the over-wintering management for aquatic livings.